To solve the system by substitution, we can first substitute the first equation into the second equation:
5x = 9x + 4
Now, let's solve for x:
4x = -4
x = -1
Now that we have found the value of x, we can substitute it back into the first equation to find the value of y:
y = 5(-1)
y = -5
Therefore, the solution to the system of equations is x = -1 and y = -5.
Question
Watch Video
Show Examples
Solve the system by substitution.
y, equals, 5, x
y=
5x
y, equals, 9, x, plus, 4
y=
9x+4
Answer
Attempt 1 out of 2
left parenthesis(
,
right parenthesis) Submit Answer
1 answer